Improving Cooperation and Self-Confidence Through Role-Playing in Group B Students of Kartika IV-17 Kindergarten, Madiun City - Dyah Astuti Widyarini (Jurnal Paradigma, 2026)
This study seeks to enhance the collaboration abilities and self-confidence of Group B pupils at TK Kartika IV-17 Madiun, which were identified as being relatively low. This deficiency resulted from the frequent application of the storytelling approach, which was once regarded as effective but, in actuality, depended largely on children's exercises (LKA) and inert listening. Observations indicated that this approach was unsuccessful in promoting collaboration and self-assurance. Therefore, this study was carried out to improve these skills through the use of role-playing techniques. This Classroom Action Research (CAR) comprised two cycles, adhering to the processes of planning, implementation, observation, and reflection. Data were gathered via observation and documentation, then analyzed to assess the enhancement in students' cooperation and self-confidence. The findings demonstrated that the role-playing technique significantly enhanced both attributes among students in Group B. Cooperation scores rose from a pre-cycle score of 108 (Poor) to 198 (Good) in Cycle I, and further increased substantially to 273 (Excellent) in Cycle II. Self-confidence scores increased from a pre-cycle score of 105 (Poor) to 213 (Good) during Cycle I, and reached 268 (Excellent) in Cycle II. Thus, the role-playing method has been demonstrated to offer an effective, collaborative, and meaningful learning experience that enhances the cooperation and self-confidence of Group B students at TK Kartika IV-17 Madiun.